The Need for Regulation of Direct-to-Consumer Genetic Testing in the United States: Assessing and Applying the German Policy Model - Sarah F. Sunderman (Washington University Global Studies Law Review, 2013)
In 2008, Time Magazine declared 23andMe’s retail DNA test the “Invention of the Year.” The actual value of this and other direct-to-consumer (“DTC”) genetic tests remains to be seen, however, and government agencies worldwide have been left to decide if and how strictly to regulate this relatively new but growing field of genetic technology. This Note explores the ever-evolving genetics testing industry, specifically DTC tests that are manufactured and marketed by private companies. Part I evaluates the arguments in favor of DTC genetic testing, and Part II assesses the concerns held by those opposed to DTC testing. After giving an overview of the current United States regulatory framework in Part III, Part IV outlines a selection of regulatory recommendations published by various American and international genetics organizations and governmental agencies. Part V then examines Germany’s regulatory approach, which results in an effective ban on DTC genetic testing. Ultimately, after addressing some proposed solutions, Part VI advocates for a regulatory approach in the United States comparable to Germany’s, though less strict and more nuanced.
Keywords: genetic testing; direct-to-consumer test; government regulation; United States; Germany